Pengaruh electronic word of mouth dan food quality terhadap keputusan pembelian - Sri Wiludjeng Sunu Purwaningdyah (Universitas Kristen Maranatha, 2019)
The development of information technology nowadays impact on rapid economic growth. It makes entrepreneurs have to upgrade their businesses thus they can compete both nationally and internationally. This condition also encourages entrepreneurs both in the manufacturing sector and especially culinary services to be able to capture a wider market share. One marketing strategy that can be used to reach consumers more broadly is through electronic word of mouth (e-WOM), to convey or inform, offer, and remind about its products. No less important is the attention of culinary entrepreneurs to pay attention to the quality of their products (food quality). The aim of this study is to find out how e-WOM and food quality capabilities influence consumer purchasing decisions at Mie Merapi in Bandung. The research method used is descriptive and quantitative methods. While the sampling method with accidental random sampling technique. The analytical tool used is multiple regression. The results showed thate-WOM was able to positively influence consumer purchasing decisions but was not significant, because e-WOM conducted by Mie Merapi was less attractive, because culinary noodles were an ordinary culinary.Food quality able to provide a positive significant influence on consumer purchasing decisions at Mie Merapi in Bandung, because consumers are more convinced about the product needed is quality. This research suggests Mie Merapi to inform and offer products through consumers testimonials that have made direct purchases, because user reference is a valuable experience and as a consideration in purchasing products. In order for this user reference to be disseminated more widely, it can be used to invite meals directly to the place by giving gifts. For example, free noodle for first five customers.